PERAN ATRIBUT PRODUK DAN SIKAP MEREK TERHADAP PENINGKATAN EKUITAS MEREK - Utami Puji Lestari; Ella Anastasya Sinambela (Universitas Mahendradatta Denpasar, 2023)
High brand equity becomes the company's strength to stay in the market competition. Increasing brand equity is one of the company's strategies that is carried out all the time. Increasing the supporting factors of brand equity is a way to strengthen brand equity. This study aims to determine the role of product attributes and brand attitudes in increasing brand equity. The research population is the consumer of the Rinnai brand gas stove. Obtained 85 respondents as research samples with purposive sampling technique. Research data obtained through the distribution of questionnaires will then be analyzed using multiple linear regression analysis. The results show that product attributes play a significant role in the development of brand equity. Furthermore, brand equity is significantly influenced by brand attitudes. Product attributes and brand attitudes have a significant role in the joint formation of brand equity.